Estudio de mercado para determinar la oferta y demanda de huevos de postura en la ciudad de Loja. - Febres Guamán, Verónica Yesenia (2012)
This study of market based on determine the supply and demand in the eggs of position Loja city, covering expectations of its consumption, to thereby identify aspects of importance for purposes of consultation of one of the main products of mass consumption; and their contribution to the local economy. Each analysis can be recognized that poultry activity brings to 13 per cent of the gross domestic product (GDP) agricultural and that eggs of higher consumption and preference are the position produced and marketed from the northern mountains of the country. It is a product of choice within the family basket for his contribution to the preparation of other foods and its economic character. The city of Loja this constituted by the parishes of San Sebastian - the Tabernacle - El Valle - Sucre, and for the study of market eggs stance is taken as a market segment the number of families in the city which is 34488 and has an average of 4 members per family, which is determined by average sample of 380 families and a population growth of 2.08%, according to data from the National Institute of statistics and census. Delimited segment of the product market and the relevant analysis is specified a potential 100% egg demand because all 380 families consume the product; on the basis of the existing actual demand those families who consume eggs of posture are 374 representing the 98.42%; While effective demand is 167 families representing the 44.65%. Lojanas families carried out the purchase of eggs from position in markets and wineries in a 74.74% in supermarkets the 19.47% and stores more near the 5.79%; the eggs of their greater preference are the Brown Shell with the 92.25%. The frequency of purchase of the product is variable, since they performed in different periods: the 27.01% buy weekly which the 43.56% purchased 10 units in each purchase; the 51.87% do so every five years and which the 40.21% buy 30 units; and finally the 21.12% makes the purchase of the product each month and which the 56.96% acquires 60 units in each purchase. Among the main reasons for the consumption of the product have to be food with the 33.42%; being pleasant to the palate with a 25.67% the 18.98% because it is a usual consumption. The most commonly consumed relative to the size of the product is the medium with a percentage of the 63.10% and presentation that is acquired is a 70.86% in buckets. The supply of the product this represented by those who distribute the product to the wholesale and bringing the product from poultry farms from the sierra norte specifically Ambato; Therefore the current supply of the product is of 6470 buckets per day and the year of 2'361550 buckets. On the basis of sales the 47.62% of bidders indicated that sales have increased; for the 38.10% have decreased while for the 1429% has been equally. The supply of the product on the market is every 15 days, where it acquires 98394 buckets per trip, provided that no period of scarcity that is usually the last quarter of the year. In relation to the presence of product in a bad state, download this is during the transportation and storage therefore has no return by suppliers; the only thing that has a value of recovery are buckets in which the product is packaged insofar as they have a cost of 0.05 cents. Through the corresponding analysis determined that there is an index of household consumption of eggs of position a year of 24.62 buckets and the rate of increase in consumption is 0.014, thereby linking these terms with the offer and real and effective claims define the non-existence of unmet demand in the market. The amount they consume eggs of posture lojanas families is 177 buckets acquiring on weekly averages per year. Detailed throughout the study and analysis of supply and demand for eggs from position specify the respective conclusions and recommendations and also attached the relevant annexes to the contribution of market research.